Information System for Internship Applications in the Yogyakarta City Communication, Informatics, and Encoding Office - Bimo Pradana; Sara Puja Kesuma; Darmanto Darmanto; Anastasia Meyliana; Diah Pradiatiningtyas (Paradigma - Jurnal Komputer dan Informatika, 2023)
The Office of Communication, Informatics and Encoding (DISKOMINFOSAN) is a Yogyakarta City government agency tasked with carrying out government affairs in the field of Communication, Informatics and Encoding to meet the needs of society in the current digital era. Needs regarding registration and internship activities or field work practices for Yogyakarta City students, DISKOMINFOSAN is needed to provide better service. Based on the data obtained from interviews with the Sub Coordinator of the Information System Planning and Implementation Substance Group explained that the apprentice registration system and apprentice activities that are currently running are not computerized so that the data cannot be managed optimally. Research is also carried out by direct observation as an active participant in internship activities so that it can analyze deficiencies and constraints on the running system. In the early stages, students must submit documents for the requirements to register for an apprenticeship directly to the agency so that it will take time. Next, students fill in the required data on the Google Form. If an internship has been accepted, students must fill in the progress and final report on the Google Form. This activity is considered inefficient for students because they have to access many Google Form links during registration and internship activities. The software development method used in this study is the Waterfall method, the framework used for application development uses the CodeIgniter framework while the software testing used is the black-box method. With the design of this website application system, it can be a solution to problems that occur in the running system for the registration process and internship activities at the Yogyakarta City Informatics and Encryption Communication Service.